Genetic polymorphism in the epidermal growth factor receptor gene predicts outcome in advanced non-small cell lung cancer patients treated with erlotinib. Issue 2 (November 2015) - Winther-Larsen, Anne; Nissen, Peter Henrik; Jakobsen, Kristine Raaby; Demuth, Christina; Sorensen, Boe Sandahl; Meldgaard, Peter
Highlights: EGFR-SNPs were evaluated in 331 Caucasian NSCLC patients with advanced disease. The SNPs were examined as predictors of clinical outcome after erlotinib treatment. 181946C>T was significantly association with higher DCR, longer PFS and longer OS. The SNP may serve as a new potential tool in treatment optimization. Abstract: Objectives: Epidermal growth factor receptor (EGFR) mutations are important predictors of treatment response to tyrosine kinase inhibitors (TKIs) in patients with non−small cell lung cancer (NSCLC). However, some patients with mutations do not respond and some patients without mutations show response. We therefore need additional biomarkers to improve the selection of these patients for treatment. A promising candidate could be germline genetic variations in the EGFR gene that can alter protein expression or function and may influence the response to TKIs. Thus, the aim of this study was to evaluate the predictive role of genetic variations in the EGFR gene in advanced NSCLC patients treated with a TKI. Materials and methods: Genotypes for −216G>T, −191C>A and 181946C>T in the EGFR gene were retrospectively evaluated by DNA sequencing and allele−specific PCR analysis in 331 Caucasian patients with advanced NSCLC. Genotypes were correlated with clinical characteristics, toxicity and outcome. A multivariate analysis was performed using Cox proportional hazards model while adjusting for clinically relevant factors including EGFR mutation status. Results: 181946CT or TT genotypes showed an association with clinical outcome compared with patients with the 181946CC genotype (disease control rate (DCR), 68% versus 52%; P  = 0.049; progression−free survival (PFS), adjusted hazard ratio (HR) = 0.74 (95% confidence interval (CI): 0.55–0.99); overall survival (OS), adjusted HR = 0.73 (95% CI: 0.54–0.97)). Subgroup analysis demonstrated that the association may be most relevant in EGFR mutation−positive patients (PFS, adjusted HR = 0.43 (95% CI: 0.22–0.82); OS, adjusted HR = 0.47 (95% CI: 0.24–0.93)). Conclusion: The 181946C>T polymorphisms in the EGFR gene seems to be a potential predictor of higher DCR, longer PFS and OS in advanced NSCLC patients treated with erlotinib, especially in EGFR mutation-positive patients. Thus, this SNP may be a new potential tool for selection of patients for treatment. Prospective randomized studies are wanted to confirm our data.